The effect of soil compaction levels on germination and biometric characteristics of coffee (Coffee arabica, L) seedlings in the nursery - Masaka, Johnson; Khumbula, N. (International Journal of Agricultural Research, 2021)
In nursery coffee seedling production, farmers often subject potted soil media to casual compaction without considering the effects of such practices on the physical properties of growing media, which significantly influence seedling emergence and biomass characteristics. A 32-week study was carried out at Chipinge Coffee Research Station (20°13’ S; 32°36’ E, elev. >1500 m above sea level), Zimbabwe. The main objective of the study was to determine the effect of different compaction levels in the nursery on the emergence and biometric characteristics of coffee. The first seedling emergence counts in the 5th week after sowing showed that seemingly insignificant bulk density increases of 5.7% (6.6 g cm-3) and 37.5% (43.28 g cm-3) in T2 and T3 potted soils above no-compaction levels triggered uncorrespondingly massive reductions of 75 and 90% in coffee seed germination, respectively. The no-compaction seedlings were 30.33 and 56.27 mm taller than those in the semi and full soil compaction pots respectively in the 21st week after sowing. No-compactioncoffee seedlings recorded 0.689-0.911 mm thicker stems than those observed in semi and full compaction pots. Semi compaction simulations reduced root mass per plant by a modest 1.88 g while full compaction in potted soil media dwarfed root biomass by a massive 5.34 g.